(untitled) (Advances in Military Technology, 2013)
The essence of this article is finding the optimal degree of the p=f(v) real photovoltaic panel characteristics approximation polynomial. The characteristics are considered as one realization of a stochastic system and it is the result of long-term measuring. The outputs are the coefficients of an approximation polynomial of an optimal degree. For its calculation, we use the well-known Euclidean norm of residues. The advantage of this approach is that it takes all the influences on the panel’s attributes into consideration (solar irradiation, temperature, aging, random effects). It is necessary for the approximation to carry out a rotation of the measured characteristics and a backwards rotation of the approximation polynomial course. This method enables us to create a mathematical or numerical model of a real photovoltaic panel of any type. All the algorithms and experiments were done using MATLAB® system.